2013
DOI: 10.2319/071712-584.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of white spot lesion formation during orthodontic treatment

Abstract: Nearly 25% of the patients developed WSLs while in treatment, depending on fluorosis, treatment time, preexisting WSLs, and oral hygiene. Orthodontists need to be mindful of these risk factors when making treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
202
2
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(237 citation statements)
references
References 14 publications
16
202
2
17
Order By: Relevance
“…The content of the FADA was informed by clinical evidence (Brin et al, 2003, Julien et al, 2013, patient experience of orthodontic treatment (Feldmann, 2014) and the findings from the interviews described above (January 2014 -March 2014) (Figure 1). …”
Section: Methodsmentioning
confidence: 99%
“…The content of the FADA was informed by clinical evidence (Brin et al, 2003, Julien et al, 2013, patient experience of orthodontic treatment (Feldmann, 2014) and the findings from the interviews described above (January 2014 -March 2014) (Figure 1). …”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown the prevalence of WSLs to fall between 25% and 97%. [14][15][16] Although 66% of general dentists believe the patient is the most responsible party for preventing WSLs, 82% place at least part of the responsibility on the orthodontist. 17 Furthermore, approximately one-third of general dentists believe the presence of multiple WSLs at the end of orthodontic treatment negatively influences their opinion of the orthodontist.…”
Section: Introductionmentioning
confidence: 99%
“…WSL are a common complication in orthodontics [11]. The incidence of patients who develop at least one new WSL during orthodontic treatment ranged from 68% to 95% [12][13][14]. WSL may develop around the bracket, their white appearance seriously compromising aesthetics [15,16].…”
Section: Population At Riskmentioning
confidence: 99%